Low ankle brachial index predicts poor outcomes including target lesion revascularization during the long-term follow up after drug-eluting stent implantation for coronary artery disease. Issue 3 (March 2020) - Sasaki, Masahiro; Mitsutake, Yoshiaki; Ueno, Takafumi; Fukami, Ako; Sasaki, Ken-ichiro; Yokoyama, Shinji; Ohtsuka, Masanori; Nakayoshi, Takaharu; Itaya, Naoki; Chibana, Hidetoshi; Sasaki, Motoki; Ishimatsu, Takashi; et al.
Highlights: Low ankle brachial index (ABI) may be a predictor of poor outcomes after drug-eluting stent treatment. Low ABI was associated with higher incidence of target lesion revascularization. Low ABI was related to higher rate of major adverse cardiac and cerebrovascular events. Abstract: Background: Peripheral arterial disease (PAD) frequently coexists with coronary artery disease (CAD). The ankle-brachial index (ABI) is widely used for the screening for PAD. Low ABI is associated with short-term clinical outcomes in patients receiving coronary drug-eluting stent (DES) implantation. However, there is no report to examine the relationship between lower ABI and long-term clinical outcomes after DES implantation. Thus, we investigated the clinical long-term impact of low ABI after DES implantation. Methods: This retrospective analysis included 181 CAD patients treated with DES from April 2010 to March 2013 in our institute. Based on ABI values, we divided the subjects into the low-ABI group (ABI < 0.9, n = 29) and the normal ABI group (0.9 ≤ ABI < 1.4, n = 152). The incidence of target lesion revascularization (TLR), all-cause mortality, and major adverse cardiac and cerebrovascular events (MACCE) defined as a composite of cardiac death, myocardial infarction, stroke, and any repeat revascularization, were compared between the 2 groups. Results: During the median follow-up period of 43 months, the incidences of TLR, all-cause mortality, and MACCE were significantly higher in the low ABI group than in the normal ABI group (TLR: 41.4% vs 9.9%, p < 0.001, all-cause mortality: 31.0% vs 3.9%, p < 0.001, MACCE: 48.3% vs 11.2%, p < 0.001, respectively). Conclusions: Low ABI may predict poor long-term outcomes, including TLR, in CAD patients treated with DES.